Changes in pregnancy-related hormones, neuromechanical adaptations and clinical pain status throughout pregnancy: A prospective cohort study - Catherine Daneau; François Nougarou; Jacques Abboud; Stephanie-May Ruchat; Martin Descarreaux (PLoS ONE, 2025)
During pregnancy, increased hormonal levels contribute to ligament laxity of the pelvis and could predispose to lumbopelvic pain. The main objective of this study was to assess changes in pregnancy-related hormones, neuromechanical adaptations and clinical pain status throughout pregnancy. An exploratory objective was to examine the possible association between those variables. Twenty-eight pregnant women participated in the study. At each trimester, they provided a blood sample (to measure relaxin, estrogen and progesterone), completed questionnaires assessing clinical status (functional disability, risk of poor prognosis of prolonged lumbar disability, avoidance behaviors, anxiety and pain catastrophizing), and were asked to perform a flexion-relaxation task (erector spinae electromyography and trunk kinematics). Results showed that throughout pregnancy, nocturnal and diurnal lumbopelvic pain intensity and related-disability, risk of poor lumbopelvic pain prognosis as well as avoidance behaviors increased, while pain catastrophizing decreased. Neuromechanical characteristics of flexion-relaxation task, including low back muscle activity and trunk kinematics, were similar across the three trimesters. Positive correlations were found between disability and estrogen levels (changes between first and second trimester, p = 0.05), and estrogen and diurnal lumbopelvic pain intensity (change between second and third trimester, p = 0.02). A positive correlation was also found between weight and the Pelvic Girdle Questionnaire score (changes between second and third trimester, p = 0.05). Negative correlations were found between weight (change between first and second trimester) and lumbopelvic maximal angle (p = 0.003), FRP onset for pelvic (p = 0.04) and lumbopelvic (p = 0.003) angles as well as FRP cessation for lumbopelvic angle (p = 0.001). These results show that, in pregnant women, pain and disability are associated with hormonal changes rather than trunk neuromechanical characteristics during a flexion-relaxation task. These results suggest that the flexion-relaxation task may not be an appropriate proxy to study vertebral and pelvic muscle control in pregnant women.